Analysis of Community Interest in Village Cooperative Unit in Nagari Tandikek - dinila arifah; Widra Firdaus; lika Akana Helmi; Syukri Rosadi (Institut Agama Islam Sumatera Barat, 2023)
This research was taken because the writer wanted to know why the Tandikek community's interest in KUD was decreasing. The purpose of this research is to find out the development of KUD Tandikek from the beginning until now and what causes the lack of interest of the Tandikek community in the services of KUD Tandikek. This research method is a qualitative method, the place of this research is KUD Tandikek, one research respondent is taken, namely KUD Tandikek employees. The research instruments used were field observations, interviews and documentation. The author uses data analysis, namely data reduction, data presentation and drawing conclusions. The research findings obtained by the author are KUD Tandikek, village unit cooperatives (KUD), namely cooperatives in rural areas that have an important role in rural communities, especially the agricultural sector. With the development of the business era, KUD Tandikek has decreased, this decline was caused by several factors including the lack of firmness from KUD Tandikek management in terms of savings and loans, many other institutions that match the activities of KUD Tandikek, BRI LINK is increasingly widespread in society. For this reason, a strategy is needed so that KUD Tandikek returns to life and develops in the midst of today's technological advances, one of which is to redevelop existing businesses in KUD Tandikek and improve services to the community by utilizing technological sophistication. From here the author can give the title Analysis of Community Interest in KUD in Nagari Tandikek, Patamuan.